Orthogonal time frequency space modulation: contribution to channel estimation and data detection in a high mobility multipath wireless enviroment - Bandeira, Dayse Gonçalves Correia (2022)
Data transmission in wireless systems brings numerous challenges, particularly in scenarios characterized by multipath propagation within rapidly changing channels in time. In this context, Orthogonal Time-Frequency Space (OTFS) modulation has recently emerged as a promising solution designed to operate effectively in doubly selective channels, encompassing variations in both time and frequency, even in high mobility scenarios. OTFS modulation entails the initial multiplexing of digital symbols in the Doppler-delay domain, subsequently transforming them into the time-frequency domain by Orthogonal Frequency Division Multiplexing (OFDM). Extensive research indicates that OTFS offers several performance advantages over conventional OFDM in many aspects, including a robust increase in data rates under high mobility conditions. Another advantage is the sparsity of the channel produced by OTFS, facilitating the utilization of low-complexity algorithms for accurate data detection. This thesis explores the performance of OTFS modulation within a doubly dispersive channel is evaluated in different versions of the message passing algorithm (MPA) in terms of computational complexity and bit error rate (BER). The findings reveal that MPA algorithms, especially their approximate versions (AMP), such as Expectation Propagation (AMP-EP) demonstrate superior performance. However, when considering the trade-off between computational complexity and BER performance, AMP simplified first-order (AMP-First Order) emerges as the optimal choice for both known and estimated channels. Methods for channel estimation are used, including the Finite Element Method (FEM) and the Natural Cubic Splines Method, both presenting good tradeoff between channel estimation accuracy and complexity. Comparative analyses between OTFS and OFDM are conducted, highlighting the advantages of OTFS, particularly within macrocell channel environment.